2020
DOI: 10.15384/kjhp.2020.20.2.49
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sleep Disturbance in Korean University Students: A Systematic Review and Meta-Analysis

Abstract: Background: This systematic review and meta-analysis aimed at investigating the current status and prevalence of sleep disturbance in Korean university students and provide evidence to develop appropriate strategies for improving sleep disturbance.Methods: Pooled prevalence of sleep disturbance in Korean university students was assessed using PubMed, CINAHL, Research Information Sharing Service, National Assembly Library, Korean studies Information Service System, and Korea Citation Index databases. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…According to a systematic review and meta-analysis, which was done to determine the global prevalence rate of poor sleep quality among university students, the result was 57% (89). The current finding is also comparable with a systematic review and a meta-analysis study conducted among Korean University Students yielded 59.2% (90). A global systematic and meta-analysis study of the general population found that 57.3% of respondents had poor sleep quality, which was consistent with the findings of the current study (91).The results of a systematic review of twelve studies among Indian university students range from 25 to 72%, which is consistent with the findings of the current meta-analysis on poor sleep quality among students in Africa (92).…”
Section: Associated Factors Of Poor Sleep Quality Among University St...supporting
confidence: 76%
“…According to a systematic review and meta-analysis, which was done to determine the global prevalence rate of poor sleep quality among university students, the result was 57% (89). The current finding is also comparable with a systematic review and a meta-analysis study conducted among Korean University Students yielded 59.2% (90). A global systematic and meta-analysis study of the general population found that 57.3% of respondents had poor sleep quality, which was consistent with the findings of the current study (91).The results of a systematic review of twelve studies among Indian university students range from 25 to 72%, which is consistent with the findings of the current meta-analysis on poor sleep quality among students in Africa (92).…”
Section: Associated Factors Of Poor Sleep Quality Among University St...supporting
confidence: 76%
“…The prevalence of insomnia among university students ranges from 7.7% to 70% across various countries using different time frames, measurements, and sampling methods [24]. A meta-analysis of 14 studies found a 48.9% overall pooled prevalence of sleep disturbance in Korean university students [25]. Because of the high prevalence of insomnia in students and the significant mental health risks associated with it, suitable screening tools could be handy.…”
Section: Introductionmentioning
confidence: 99%
“…In South Korea, research on chilly climates is rare. According to Hwang (2020), 75% of the research on female engineering students deals with career-or academic-related topics, and 75% of the research methods used are quantitative. Allan and Madden (2006) stated that an appropriate research method is crucial when studying a subtle subject, and quantitative methods, such as surveys, may not yield a complete picture.…”
Section: Introductionmentioning
confidence: 99%